"Elderqueer is more than just an age thing": Experiences of LGBTQ+ intergenerational co-presence on TikTok - Jamet-Lange, Hannah; Nešovic, Dunja; Duguay, Stefanie (AoIR Selected Papers of Internet Research, 2026)
While TikTok has garnered much attention for its rapid uptake by youth, it has also seen adoption by older age demographics. Given social media’s longstanding importance for convening LGBTQ+ publics and the rarity of intergenerational offline spaces, this paper examines the intersection of age and sexual identity on this short-video platform. It does so through qualitative analysis of 23 semi-structured interviews with elderqueer TikToker users. Findings indicate that participants experience age as an ambiguous identity marker due to TikTok’s affordances for rendering its expression fluid and LGBTQ+ approaches to life course stages as less rigid than heteronormative milestones. Despite this ambiguity of age, participants found TikTok’s algorithmic curation and passive viewing features inhibited the formation of interpersonal connections across generations. They attempted to overcome these constraints by contributing, and engaging with, personal narratives sharing about past resilience and present life as an elderqueer while drawing inspiration from younger LGBTQ+ people. These preliminary findings illustrate how TikTok’s affordances and individuals’ fluid expressions of age alongside personal narratives of sexual identity give rise to an intergenerational co-presence that recognizes struggles of the past while giving hope for the future.